Does PSA reduction after antibiotic therapy permits postpone prostate biopsy in asymptomatic men with PSA levels between 4 and 10ng/mL? - Busato,W. F. S. (2015)
Purpose We investigated the effect of antibiotics on PSA in asymptomatic patients with mild PSA elevation. Materials and Methods We prospectively evaluated, in a non-randomized design, 106 asymptomatic patients with PSA of 4-10ng/mL, with a negative digital rectal examination and with no urinary tract infection evidence for 2 years. Patients were divided into two groups: those treated with antibiotics for 3 weeks (G1) and those who were not treated (G2). PSA was taken six weeks after and prostate biopsy was performed in all patients. Results PCa was diagnosed in 25 of 106 patients (23.6%): 16 (25.0%) in G1 and 9 (21.4%) in G2 (p>0.05). PSA normalization was experienced in 24.5%. In G1, PSA returned to <4ng/mL in 15 (23.4%) patients compared to 11 (26%) patients in G2. In the patients with a positive biopsy, no significant variation was noted in PSA, fPSA, %fPSA and DPSA after antibiotic treatment. A significantly lower cancer detection rate was noted with decreased PSA, fPSA, and DPSA after antibiotic use. A PSA reduction rate of ≥10% occurred in 58.5%, and this was similar in both G1 and G2 groups. The sensibility, specificity and accuracy of PSA reduction of ≥10% were 31%, 23% and 25%, respectively. Conclusion Empirical antibiotic therapy in asymptomatic male patients is not related to PSA reduction. The greater than 10% PSA reduction after antibiotic in this population cannot postpone prostate biopsy.